Serratia inhibens sp. nov., a new antifungal species isolated from potato (Solanum tuberosum). Issue 7 (17th July 2020) - Hennessy, Rosanna C.; Dichmann, Søs I.; Martens, Helle Juel; Zervas, Athanasios; Stougaard, Peter
Abstract : A novel bacterial strain, S40 T, with strong antifungal activity was isolated from the rhizosphere of green potato collected from Zealand, Denmark. Polyphasic analysis with a combined phenotypic, phylogenetic and genomic approach was used to characterize S40 T . Phylogenetic analysis based on the 16S rRNA gene and MLSA (concatenated gyrB, rpoD, infB and atpD sequences) showed that strain S40 T was affiliated with the genus Serratia and with Serratia plymuthica PRI-2C as the closest related strain [average nucleotide identity (ANI), 99.26 %; DNA–DNA hybridization (dDDH), 99.20%]. However, whole genome sequence analyses revealed that S40 T and S. plymuthica PRI-2C genomes displayed lower similarities when compared to all other S. plymuthica strains (ANI ≤94.34 %; dDDH ≤57.6 % relatedness). The DNA G+C content of strain S40 T was determined to be 55.9 mol%. Cells of the strain were Gram-negative, rod-shaped, facultative anaerobic and displayed growth at 10–37 °C (optimum, 25–30 °C) and at pH 6–9 (optimum, pH 6–7). Major fatty acids were C16 : 0 (27.9 %), summed feature (C16 : 1 ω 6 c /C16 : 1 ω7 c ; 18.0 %) and C17 : 0 cyclo (15.1 %). The respiratory quinone was determined to be Q8 (94 %) and MK8 (95 %) and the major polar lipids were phosphatidylethanolamine and phosphatidylglycerol. The results of phenotypic, phylogenetic and genomic analyses support the hypothesis that strain S40 T represents a novel species of the genus Serratia, for which the name Serratia inhibens sp. nov. is proposed. The type strain is S40 T (=LMG 31467 T =NCIMB 15235 T ). In addition, we propose that S. plymuthica PRI-2C is reclassified and transferred to the species S. inhibens as S. inhibens PRI-2C.